PERAN PRODUSER DALAM PEMBUATAN FILM PENDEK “GAGAL PAHAM” - Sarah Sausan Abani; Arryadianta (ADISAM PUBLISHER, 2025)
Film is a combination of visual elements from various forms of art such as music, visual arts, and sound art, brought together by technological advancements. Aside from serving as a tool to express events, films are also used as an effective communication medium for audiences. There are various types of films, one of which is short film. A short film is a concise presentation with a short duration, yet it possesses a distinctive and complex atmosphere that captivates the audience. The work intended for this final project is a short film titled